Synergistic Catalysis of Ruthenium Nanoparticles and Polyoxometalate Integrated Within Single UiO−66 Microcrystals for Boosting the Efficiency of Methyl Levulinate to γ-Valerolactone - Cai, Xiaoxiong; Xu, Qionghao; Tu, Gaomei; Fu, Yanghe; Zhang, Fumin; Zhu, Weidong (Frontiers in Chemistry, 2019)
The synthesis of heterogeneous cooperative catalysts in which two or more catalytically active components are spatially separated within a single material has stimulated considerable research efforts. The multiple functionalities of catalysts can significantly improve the efficiency of existing organic chemical transformations. Herein, we introduce ruthenium (Ru) nanoparticles (NPs) on the surfaces of a metal–organic framework pre-encapsulated with polyoxometalate silicotungstic acid (SiW) UiO–66 (University of Oslo [UiO]) and prepared a 2.0% Ru/11.7% SiW@UiO–66 porous hybrid using the impregnation method. The close synergistic effect of metal Ru NPs, SiW and UiO-66 endow 2.0% Ru/11.7% SiW@UiO-66 with increased activity and stability for complete methyl levulinate (ML) conversion and exclusive γ-valerolactone (GVL) selectivity at mild conditions of 80 °C and at a H2 pressure of 0.5 MPa. Effectively, this serves as a model reaction for the upgrading of biomass and outperforms the performances of the constituent parts and that of the physical mixture (SiW + Ru/UiO–66). The highly dispersed Ru NPs act as active centers for hydrogenation, while the SiW molecules possess Brønsted acidic sites that cooperatively promote the subsequent lactonization of MHV to generate GVL, and the UiO–66 crystal accelerates the mass transportation facilitated by its own porous structure with a large surface area.